2011
DOI: 10.1002/ijfe.454
|View full text |Cite
|
Sign up to set email alerts
|

Socially Responsible Investing in the Global Market: The Performance of Us and European Funds

Abstract: This paper investigates the style and performance of US and European global socially responsible funds. Several specifications of the return-generating process are applied as well as their corresponding conditional versions.Most European global socially responsible funds do not show significant performance differences in relation to both conventional and socially responsible benchmarks. US funds and Austrian funds show evidence of underperformance. By applying conditional models, we find evidence of time-varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 45 publications
9
58
1
Order By: Relevance
“…Evidence of a momentum effect is found in North America, while a contrarian strategy is found to add value to SRI funds in Europe. This result is consistent with Cortez et al (2012), who found that there is a momentum effect in United States SRI funds. In terms of the Carhart-α value, North American SRI funds perform better than European SRI funds.…”
Section: Resultssupporting
confidence: 92%
“…Evidence of a momentum effect is found in North America, while a contrarian strategy is found to add value to SRI funds in Europe. This result is consistent with Cortez et al (2012), who found that there is a momentum effect in United States SRI funds. In terms of the Carhart-α value, North American SRI funds perform better than European SRI funds.…”
Section: Resultssupporting
confidence: 92%
“…Over the full period of investigation, green mutual funds experience a significant small company effect. Small cap and growth stocks face less environmental risks and presumably the funds' holdings are tilted towards innovative environmental pioneers (see Cortez et al 2012;Kreander et al 2005). Likewise, the green fund portfolio is highly exposed to growth stocks.…”
Section: Insert Table X About Herementioning
confidence: 99%
“…SR funds in Germany mostly practice negative screening and/or follow a best in class investment approach (see FNG (2014)). When the performance of SR and conventional retail funds domiciled in Germany are compared, no significant underperformance of SR funds can be found (Cortez et al 2009(Cortez et al , 2012Renneboog et al 2008;Kreander et al 2005;Bauer et al 2005;Schröder 2004;Kreander et al 2002)). Globally, there are more than 100 studies concerning the performance of SR funds (e.g., Chegut et al 2011;Rathner 2013;von Wallis and Klein 2014).…”
Section: Introductionmentioning
confidence: 98%